Potentials of wetted fabric as a cold medium for transport of horticultural products. - Nattawut Chaomuang; Denis Flick (SPIRE - Sciences Po Institutional REpository, 2022)
International audience
Keywords: Plant Surface Properties and Treatments; Textile materials and evaluations